Introduction: New Directions, New Approaches - Mendes, Ana Cristina (2018)
The study of diaspora, as both a migratory experience and a theoretical concept associated with unfixity and in-betweenness, liminality and hybridity, travel and displacement, nomadism and touring, has gone through a number of transformations since its intellectual heyday in the 1990s. Much of the first decade of diaspora scholarship set out to define, and (very often, even if unwittingly) police the boundaries of the term. Whereas diaspora studies has grown exponentially in the last decades, there is still an untapped critical potential related to new forms of movement across the globe and new experiences of “diaspora space” (Brah 1996). Disrupted by war, conflict and poverty, populations continue to be on the move. This volume does not intend to rehearse what is by now familiar territory in diaspora studies, but is rather interested in opening up new lines of inquiry by placing diaspora in dialogue with other fields and approaches and reassessing its usefulness in light of the pressing issues of the twenty-first century. Therefore, as well as exploring the new ways that diaspora can be deployed to make sense of our contemporary moment, this book also considers some of the limitations of the term and its potential alternatives. Indeed, many of our contributors employ a number of formulations, including transculturalism and interculturalism (Flockemann), transnationalism (Waegner, D’Souza), globalization (Deandrea), cosmopolitanism (Steckenbiller) and planetarity (Steckenbiller, Rochester) as both complements to and critical interlocutors with “diaspora”.